THE MECHANISMS OF THE DISORDERS OF MOTOR-EVACUATION FUNCTION OF GALL BLADDER AND THEIR IMPORTANCE IN THE DEVELOPMENT OF CHOLELITHIASIS - Ya. M. Vakhrushev; N. A. Khokhlacheva; P. S. Mikheevа; E. V. Suchkova (SINAPS LLC, 2018)
The aim of the study was to study the role of gastrin in disturbing the motor-evacuator function of the gallbladder and the biochemical properties of bile in cholelithiasis.Material and methods. 230 patients with pathology of the biliary system were examined. In verification of the diagnosis, in addition to general clinical data, the results of ultrasound investigation of the  hepatobiliary system were used. Cholecystometry and dynamic hepatobiliary scintigraphy were used to study the functional state of  the gallbladder. In various variants of the motor-ejaculatory function  of the gallbladder, a study was made of the biochemical properties of bile (cholesterol, bile acids, cholate-cholesterol coefficient) obtained  as a result of multifraction duodenal sounding. The level of the  gastrointestinal hormone gastrin in the peripheral blood was  determined by the enzyme immunoassay.Results. With ultrasound, 78% of the patients in the US are diagnosed with signs of biliary sludge. In 75.4% of cases with microscopy of the same species, crystals of cholesterol and  calcium bilirubin were detected. The study of the biochemical  composition revealed an increase in cholesterol, a decrease in bile  acids and a cholate-cholesterol coefficient in portions B and C of bile. Disturbances of motorevacuation function of the gallbladder, which are one of the pathogenetic factors of cholelithiasis, were detected in 72% of the patients examined. In patients, the level of gastrin was  reduced, and to a greater extent - with gallbladder hypomotorism.  The significant role of gastrin in changing the functional state of the  gallbladder and, therefore, in the formation of lithogenic bile is  established by the method of correlation analysis. The conclusion.  Investigations of the parameters of the motor function of the HP and the biochemical properties of bile on the one hand and the level of the gastrointestinal hormone gastrin on the other have shown the important role of hypogastrinemia in the formation of lithogenic bile by suppressing the emptying of the HP.